Simulation of Digital Modem Based on Software Defined Radio (SDR) (مجلة المنصور, 2022)
The Radio Frequency (RF) transceiver performs various functions and the use of software defined radios (SDRs) is increasing day after another. The SDRs are characterized by their flexibility where the software can change the functionality of the device without changing its hardware. This paper presents a flexible SDR-based communication system. The simulated system has the ability to perform the following modulation / demodulation modes: AM, DSB, SSB, QAM, FM and PM. These modes are achieved by software at the baseband frequency components that are in-phase component (I) and quadrature phase component (Q) in accordance to the modulator / demodulator instead of achieving this process digitally at IF or RF frequency directly. The simulated results proved the efficiency of the implemented system in case of noiseless or noisy channel. To simplify the use and evaluation of the proposed system a Graphical User Interface (GUI) has been implemented for the system.